EMPTY CHAIR THERAPY TO REDUCE DEPRESSION AND ANXIETY SYMPTOMS IN EARLY ADULT ADJUSTMENT DISORDER - Nabilah, Igriya Fauzi (CV. Causalita Dynamic Solutions, 2025)
Adjustment disorder is a reaction in the form of excessive emotions or behavior to an event or change in life that causes stress. There are many triggers for adjustment disorders, and each individual has their own vulnerability factors such as the death of someone important in life, loss of a job, and many other factors. In this study, adjustment disorders were caused by many events in the subject's life that came together, including the loss of several family members due to exposure to the Covid-19 virus, requests from the school to transfer children to another school, and getting pressure to complete doctoral education from the campus. Several events experienced by the subject caused stress but the subject was unable to manage the emotions and stress he experienced properly. Based on the results of the assessment using observation, interviews, and psychological tests, it was found that the subject had an adjustment disorder. The intervention chosen in this study was adjusted to the conditions and symptoms experienced by the subject. The intervention given was empty chair therapy. In this intervention method, the subject is facilitated to express emotions that have been suppressed, because so far the subject has not been able to manage his emotions properly. Empty chair therapy also provides a dialogue space for the subject to talk to themselves, express what they feel, express what is their burden in the hope that the subject can find themselves again as before. The results of the intervention carried out stated that the results were very significant and had a good impact, the subject expressed that he felt more relieved and could get out of the introjection process.